Letter from the Editor-in-Chief - Chicheł, Adam (Journal of Contemporary Brachytherapy, 2021)
Finally, it happened! Although it was a hybrid Congress, it was my pleasure to take part in the ESTRO 2021 onsite. Many thanks to the local and ESTRO organizers, especially for making it accurate despite the pandemic. The visit to Madrid was inspiring, informative, and sociable at last. Nothing can replace face-to-face discussions and personal interaction. I am sure that online access for those unable to travel at the time of the event was also priceless.